2009
DOI: 10.1111/j.1365-3059.2009.02084.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combining two genes for partial resistance to Barley yellow dwarf virus‐PAV (BYDV‐PAV) derived from Thinopyrum intermedium in wheat

Abstract: In this study two sources of resistance to Barley yellow dwarf virus (BYDV), both originating from Thinopyrum intermedium, were combined in a single genotype, line ZT, using GISH (genomic in situ hybridization) and a new molecular marker of the partial resistance gene Bdv2. Susceptible wheat cv. Sunstar, the translocation line TC14 carrying Bdv2, the addition line ZH with the group-2 chromosome arm carrying resistance, and line ZT with both resistances were inoculated with five strains of Barley yellow dwarf v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…1, 2). Similar observations were made by Jahier et al (2009) in wheat by combining Bdv2 and the group-2 chromosome arm carrying BYDV resistance derived from Thinopyrum intermedium. In their studies, they also found a very low virus titre and a signiWcantly lower number of infected plants in those lines carrying both genes compared to the single loci.…”
Section: Discussionsupporting
confidence: 77%
“…1, 2). Similar observations were made by Jahier et al (2009) in wheat by combining Bdv2 and the group-2 chromosome arm carrying BYDV resistance derived from Thinopyrum intermedium. In their studies, they also found a very low virus titre and a signiWcantly lower number of infected plants in those lines carrying both genes compared to the single loci.…”
Section: Discussionsupporting
confidence: 77%
“…However, most focused on pathogen control over short periods of time (one or a few crop seasons or a limited number of pathogen generations) and did not take into account that the pathogen population might evolve (e.g., Brown et al, 1996; Porter et al, 2000; Maqbool et al, 2001; Jahier et al, 2009; Tan et al, 2010; Brunner et al, 2012; Obala et al, 2012; Zeller et al, 2012; Cingel et al, 2014; McCarville et al, 2014; Rule et al, 2014; Vu et al, 2014; Fukuoka et al, 2015). These comparative studies did not actually compare the durability of resistance genes.…”
Section: Comparisons Of Strategies For the Short-term Control Of Pathmentioning
confidence: 99%
“…Likewise, inferences about genomic similarities amongst closely related or related species can be performed with the application of GISH, thereby making evolutionary and phylogenetic studies possible (Lim et al, 2000b). The application of GISH in plant breeding programs has made the study of chromosomal introgression possible once it exhibits, for example, the karyotype formation of backcrossed hybrids (Jahier et al, 2009).…”
Section: Introductionmentioning
confidence: 99%